Venenum bufonis: An overview of its traditional use, natural product chemistry, pharmacology, pharmacokinetics and toxicology. (12th June 2019) - Wei, Wen-Long; Hou, Jin-Jun; Wang, Xia; Yu, Yang; Li, Hao-Jv; Li, Zhen-Wei; Feng, Zi-Jin; Qu, Hua; Wu, Wan-Ying; Guo, De-An
Abstract: Ethnopharmacological relevance: The animal medicine of Venenum Bufonis (VB), a product of the secretions of Bufo gargarizans Cantor or B. melanostictus Schneider, has long been used as a traditional Chinese medicine (TCM) for the treatment of sunstroke and faint, acute filthy disease - abdominal pain or vomiting and diarrhea, etc. Aim of the review: This review is aimed at providing the comprehensive and up-to-date information of VB as regards its ethnopharmacological uses, constituents and their metabolism, pharmacokinetics, pharmacology and toxicology, all of which could be used as fundamental data for future research as well as development of new drugs. Materials and methods: The information and data about the studies of VB were collected from scientific journals, material medica, historical documents, library, and electronic databases (PubMed, Google Scholar, Science Direct, Researchgate, Web of Science and CNKI). Results: To date, about 142 bufadienolides and 16 indole alkaloids have been isolated from VB in total. The extract and isolated compounds showed a wide range of in vitro and in vivo pharmacologic effects, such as cardiotonic, anti-tumor, antinociceptive, anti-inflammatory, anesthetic and antimicrobial activities. Especially, bufadienolides have been extensively studied due to its powerful anti-tumor activities against various cancer cells. Furthermore, their metabolites and metabolic pathways were concluded in detail, and the main metabolic pathways of bufadienolides were hydroxylation, 3-isomerization, 3-keto, 16-hydrolyzation, 3-O-sulfate and 3-O-glucuronide. Conclusions: Although VB possesses significant anti-tumor effect against various cancer cell lines, the development of new drugs still remains to be a challenge due to its pharmacodynamic effects in vivo, druggability and toxicology. The main problem lies in its side effects in vivo, poor bioavailability, fast metabolism, cardiotoxicity and neurovirulence. Besides, studies on its metabolism and toxicology in vitro and in vivo, as well as clinical trials should be further conducted for the new drug development and the establishment of optimal dosage of consumption of its administration. Graphical abstract: Image 1